(untitled) (Journal of actual problems of jurisprudence, 2019)
This trip took place through personal contacts of the Dean of the law school doctor of law.N., Professor Daulet Baydeldinov Lakovich, which signed an Agreement in the conduct and organization of the international conference "the Ratio of foreign investment to environmental law " in Almaty in the project funded by the Fund "Volkswagen" Law and foreign investments in Azerbaijan, Kazakhstan and Russia: ratio and difference".